Message from the President of the United States, transmitting, in response to Senate resolution of January 2, 1889, a report upon the seal fisheries in the Bering Sea [electronic resource]. - United States. President (1885-1889 : Cleveland). ([Washington? : s.n., 1889)
Caption title. At head of title : 50th Congress, 2d session, Senate. Ex. Doc. No. 106. Electronic reproduction. Mode of access: Internet. 44